Strengthening the Use of Information Technology in Management Practices and Effective School Promotion Strategies - Rifai, Akhmad Tegar; Amalia, Nur; Indah, Tiara; Ifani, Muhammad Zulfi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta, 2024)
This study aims to investigate the management practices and promotion strategies implemented by the principal at Karungan 2 elementary school. A qualitative approach was used in this study, with data collection through interviews, observations and document analysis. Using qualitative methods makes it easier for researchers to process the data taken. The first objective is to describe school management practices, and the results of the analysis show that teacher resource management still needs to be improved, while curriculum planning and the organisation of extracurricular activities have been done well. The second objective was to identify the promotional strategies implemented, and the findings showed success in co-operation with the school committee and participation in community activities, although there was a need to improve parental involvement and communication with the surrounding community. The discussion of the findings involved expert opinions and a review of journal articles, underlining the importance of judicious budget allocation and parental involvement in effective school promotion. This research provides valuable insights for the improvement and development of school management and promotion practices at Karungan 2 elementary school.